Studies in the thiophenol mediated substitution and reductive dehalogenation of 3 bromoacetylcoumarins - Magwenzi, Faith N (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
A previous study conducted by our group identified indolyl-3-ethanone-a-thioethers (2.1a and 2.1b) as non-toxic, nanomolar, in vitro inhibitors of Plasmodium falciparum. Since the coumarin scaffold is associated with numerous biologically active compounds including antiprotozoal, anti-viral, anti-bacterial, and anti-inflammatory agents we were prompted to investigate coumaryl-3-ethanone-a-thioethers (2.1c) inspired by the activity of 2.1a and 2.1b against P. falciparum. We proposed a three-step synthesis of our target compounds 2.1c. The first step involved the Knoevenagel synthesis of 3-acetyl coumarins (2.3.1a - e) followed by a selective a-bromination to yield 3-bromoacetyl coumarin (2.2a). The final proposed step involved the nucleophilic displacement of the bromine by appropriately substituted thiophenols in either the presence or absence of base (K2CO3). Our initial findings revealed an unexpected major reductive dehalogenation of 2.2a into 2.3.1a. Further investigation revealed a close relationship between the electron withdrawing or donating nature of the thiophenol substituents and the relative formation of nucleophilic substitution or reductive dehalogenation products. Desired thioether products were obtained in higher yields when thiophenol was substituted with electron donating groups i.e. more nucleophilic thiophenols, while conversely, electron withdrawing substituents (i.e. lowered nucleophilicity) resulted in an increase of reductive dehalogenation. Furthermore, these results were consistent when experiments were conducted using either 2 or 1.2 equivalents of thiophenols which was an important observation in the context of two previous studies, by Oki et. al. and Israel et. al. Oki proposed that dehalogenation of a-chloro carbonyls occurs via sequential nucleophilic displacement of a-thioethers, while the study of Israel concluded that the dehalogenation of a-iodo carbonyls occurred in a single discreet step. Finally, in an effort to enhance nucleophilic substitution through the addition of K2CO3, we observed a Robinson annulation resulting in previously undescribed C-8 thiophenol functionalised dibenzo[b,d]pyran-6-ones (3.4a - e). In the introduction to this thesis, we briefly summarise the utility of coumarins in medicinal chemistry and related fields. Chapter two describes the rationalisation of our original research question and a retrosynthetic analysis of our desired compounds, followed by an initial description of the unexpected reductive dehalogenation. Chapter 3, begins with a brief review of reductive dehalogenation of a-halocarbonyls, and is followed by an analysis and discussion of our results in the context of the studies by Israel et. al. and Oki et. al.
Keywords: 3-bromoacetylcoumarins; Coumarins; Halogens -- Decontamination; Thiols; Plasmodium falciparum; Malaria -- Chemotherapy